El régimen municipal en la óptica jurídico-constitucional (1949-1999) - Araya Pochet, Carlos (2000)
The author analyzes the characteristics of the Costa Rican municipal sistem prior to the 1949 constitution, as a preamble to presenting the features of the municipal system under the current constitution and discussing the functioning of municipalities from 1949 to the present.